Номінативна деривація назв осіб у західнополіських говірках - Павленко, Лариса Петрівна; Pavlenko, Larysa P. (Волинський національний університет ім. Лесі Українки, 2008)
У статті проаналізовано специфіку номінативної деривації назв осіб у західнополіських говірках української мови. The nominative derivations of person names in the Western Ukrainian modes of dialects the Ukrainian language are analyzed in the article.
Nominative derivation of person names in the western ukrainian modes of dialects
Keywords: назви осіб; номінативна деривація; система українського словотвору; питомі й запозичені слова; аналітичні словосполучення; західнополіські говірки української мови; person names; nominative derivation; the system of the Ukrainian word building; interrogative and negative words; analytical word combinations; Western Polyssian modes of dialects of the Ukrainian language